Evaluasi Ergonomi Berdasarkan Workload Analysis Dan Postur Kerja Pada Proses Batik Cap (Studi Kasus Ukm Batik Cap Supriyarso) - Pambudi, Wisnu Setyo; , Hafidh Munawir, ST, M.Eng (2017)
This study discusses the evaluation of the load and work postures in the process of batik pattern stamp in SMEs Batik Cap Supriyarso. At work stations where there are 6 workers entire activity was still traditional and manual. Workers make patterns with the help of the stamp, and weigh between 0.5-1 kg cap. Total production lots and manufacturing process as well as the position of the monotonous work that can cause fatigue and boredom by craftsmen. In the data processing method% CVL researchers to analyze the physical load, NASA-TLX to determine the mental burden. While to analyze the working posture researchers used a method RULA assisted with CATIA V5R20. The results of physical load calculations using the% CVL obtained a final score of 29,2 where this value is not the case in the category of fatigue. From the results of the mental load calculations using the NASA-TLX workload obtained average is 48,1 incoming workers on the type of workload rather high. Indicators of physical needs have the highest average when compared to the six indicators. While working posture analysis obtained two working posture with the highest level 7 which should be improved posture. Three other posture is worth 3 and 4 are included in the category needs to be investigated in the work posture.